Recent development in stratigraphic forward modelling and its application in petroleum exploration - Huang, X.; Griffiths, Cedric; Liu, J. (2015)
© 2016 Geological Society of Australia In order to better predict the geometry and spatial distribution of reservoir facies and permeability barriers, it is critical to understand stratigraphic geometries and architecture at all scales within a basin. Stratigraphic forward modelling (SFM) allows geologists to forward project the deposition and evolution of sedimentary facies within a stratigraphic framework with given prior boundary conditions. The method can approximate depositional processes while taking into consideration a range of factors that affect basin evolution and sedimentation. This paper presents an overview of recent developments in stratigraphic forward models that are currently available and have been successfully employed in simulating stratigraphic development, including geometric models, diffusion models, Fuzzy Logic models and hydraulic models. In addition, the paper discusses SFM used in the simulation of the behaviour of natural sedimentary systems and verification of the potential for hydrocarbon entrapment and accumulation in a basin using an example from the Ordos Basin, western China.